High-strength zirconium oxide composite ceramic product and preparation process thereof

By mixing wet ball milling with zirconia, silicon nitride, zirconium boride and carbon nanotubes, and mixing the molten adhesive with the powder in a roller-type glue mixer, the feed is formed and pressurized. Degreasing and sintering, and finally coating TiAlN film on a multi-arc ion coating machine to prepare high-strength zirconia composite ceramic products, which solves the problem of easy deformation or cracking of ceramic products during molding and improves the overall strength of the ceramics.

CN119390445AInactive Publication Date: 2025-02-07YIXING MINGHAOTE CERAMIC TECH CO LTD

Patent Information

Application Number
CN202411675327.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, various inorganic materials such as zirconia are prone to deformation or cracking in the hot press forming process, and ceramic products after adding binder or degreasing have problems with low strength.

Method used

Compound ceramic powder is prepared by mixing wet ball milling of zirconia, silicon nitride, zirconium boride and carbon nanotubes, and heat the molten adhesive and the powder in a roller-type glue mixer to form a feeding material After that, pressurized molding, degreasing and sintering are carried out, and TiAlN film is coated on a multi-arc ion coating machine to prepare high-strength zirconia composite ceramic products.

Benefits of technology

It improves the strength of zirconia ceramics in high temperature environments, enhances its fracture toughness and density, solves the problem of easy deformation or cracking of ceramic products during molding, and improves the overall strength of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390445A_ABST
    Figure CN119390445A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength zirconia composite ceramic product and a preparation process thereof, and belongs to the technical field of ceramics. In the prior art, ceramics prepared from various inorganic materials such as zirconium oxide are easy to deform or crack in a hot press molding process; although the forming capacity of the powder can be improved by adding the binder, the technical problem that the strength of the ceramic product added with the binder and degreased is reduced exists. A preparation process of a high-strength zirconium oxide composite ceramic product comprises the following steps: mixing zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes, and carrying out wet ball milling to obtain composite ceramic powder; mixing the composite ceramic powder and the binder mixture to obtain feed; carrying out pressure forming, degreasing and sintering on the feed to obtain a ceramic green body; the ceramic green body is subjected to metal ion injection and surface coating to obtain the high-strength zirconium oxide composite ceramic product. The prepared composite ceramic product is stable in forming structure and high in strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a high-strength zirconium oxide composite ceramic product and a preparation process thereof. Background Art

[0002] Ceramics refer to all kinds of materials and products made from clay as the main raw material and other natural mineral raw materials through processes such as crushing, mixing, molding, and sintering. Zirconia has excellent mechanical properties, high temperature resistance, and good ionic conductivity. It is an important industrial material. Ceramics based on zirconia have the advantages of high melting point and stable chemical properties.

[0003] Patent application CN108358628A discloses a mullite-zirconia composite ceramic and a preparation method thereof. Alumina, silicon dioxide, zirconium dioxide and titanium dioxide are mixed as raw materials; the raw materials are sequentially subjected to wet ball milling and hot pressing sintering to obtain mullite-zirconia composite ceramics. The composite ceramic prepared by the present invention has excellent mechanical properties and fracture toughness. However, the shapes of various inorganic materials are irregular, and simple mixing and hot pressing molding are prone to deformation or cracking during the molding process, which is not suitable for the production of ceramic products with complex shapes.

[0004] Patent application CN113735601A discloses a nano-zirconia composite material for injection molding, its preparation method and application. The injection molding ability of the powder is improved by a unique binder formula, a specific ratio of binder to powder and process conditions, thereby improving the technical problem of poor dimensional stability of ceramic products. However, if the ceramic powder with a binder is not degreased, the strength of the finished ceramic product will be reduced. After the ceramic powder is degreased, pores are easily generated, which will also damage the strength of the ceramic product.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength zirconia composite ceramic product and its preparation process, which is used to solve the problem that the mixing of various inorganic materials such as zirconia in the prior art is prone to deformation or cracking during the hot pressing molding process; although the addition of a binder can improve the molding ability of the powder, the ceramic products after adding a binder or degreasing have low strength.

[0007] The purpose of the present invention can be achieved through the following technical solutions: A preparation process of a high-strength zirconium oxide composite ceramic product comprises the following steps: S1, mixing zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes, and wet-milling them to obtain a composite ceramic powder; S2, the binder mixture is placed on a roller rubber mixer and heated to melt until the binder mixture is completely melted, and the roller temperature is set to 100-105°C; then the composite ceramic powder is added and mixed at a mixing temperature of 120-130°C to obtain feed; the feed is pressurized, degreased, and sintered in a nitrogen atmosphere to obtain a ceramic body; The binder mixture is completely melted on a roller rubber mixer in advance, and then the composite ceramic powder is added and mixed to obtain a feed material. The feed material is transferred to a mold for compression molding to obtain a green body after molding; the green body after molding undergoes heat preservation and degreasing at different temperature stages, so that the binder mixture is completely volatilized. After the green body is degreased, the strength of the body is reduced, and it becomes a porous formed body. After the sintering process, a ceramic body is prepared.

[0008] S3. The ceramic body is transferred to a metal ion implanter, and He ions and B ions are implanted in sequence, with the implantation depth of He ions being 1.25-1.29 μm and that of B ions being 0.7-0.8 μm, to obtain a ceramic body after metal ion implantation. The ceramic body after metal ion implantation is placed on a multi-arc ion plating machine for coating, with the film layer being a 25-30 mm thick TiAlN film, to obtain a high-strength zirconia composite ceramic product.

[0009] The ceramic body is injected with two metal ions in sequence, and the two metal ions are allowed to penetrate into the body by utilizing the pore structure, and the actual depth is greater than the injection depth; and then a film is plated on the surface of the ceramic body, which is a high-strength zirconium oxide composite ceramic product prepared by the present invention.

[0010] Furthermore, in step S1, the ratio of zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes is 70-80:5-10:1-5:1-5 in parts by weight; the ball milling speed is 25-30 r / min, the ball milling time is 10-12 h, the ball milling medium is water, and the ratio of balls, materials and water is 4-8:1:0.5-1.

[0011] With zirconium oxide as the matrix, a small amount of silicon nitride, zirconium boride and carbon nanotubes are added to obtain composite ceramic powder. When wet ball milling is used, water is used as the medium; the components of the composite ceramic powder used are all hard raw materials, and the amount of water needs to be reduced; in addition, the fineness of the ground powder can be increased by appropriately extending the ball milling time and increasing the ball-to-material ratio.

[0012] Furthermore, in step S2, the method for preparing the binder mixture comprises the following steps: in parts by weight, 5-10 parts of polyethylene wax, 3-5 parts of methyl acrylate and 3-5 parts of ethyl acrylate are uniformly mixed to obtain a binder mixture.

[0013] The polyethylene wax and the acrylate oligomer are mixed to obtain a binder mixture with a low melting point and strong fluidity. The binder mixture has good encapsulation properties with the composite ceramic powder.

[0014] Furthermore, in step S2, the ratio of the binder mixture to the composite ceramic powder is 10-15:80-85 in parts by weight, and the mixing time is 25-30 min.

[0015] Furthermore, in step S2, the pressure of the pressurized molding is 130-150 MPa; the degreasing is staged degreasing: the first stage is heated from room temperature to 100°C and kept warm for 50-100 min, and the second stage is heated from 100°C to 300°C and kept warm for 30-50 min, and the heating rate is 5-10°C / min.

[0016] The debinding rate is directly controlled by the temperature. By setting the debinding temperature and debinding time at different stages, the binder mixture is completely volatilized in the ceramic body, and a small amount of interconnected channels are formed in the microscopic and macroscopic structures.

[0017] Furthermore, in step S3, the He ion implantation energy is 500 keV and the implantation dose is 1×10 17 -5×10 17 / cm -2 The implantation energy of B ions is 500 keV and the implantation dose is 1×10 16 / cm -2 -5×10 16 / cm -2 .

[0018] Furthermore, in step S3, the coating temperature is 400-450° C., the coating pressure is 1-10 Pa, and the coating time is 30-50 min.

[0019] As another aspect of the present invention, a high-strength zirconia composite ceramic product is prepared by a preparation process of a high-strength zirconia composite ceramic product.

[0020] The present invention has the following beneficial effects: 1. Silicon nitride and zirconium boride have high temperature stability and strong mechanical properties. Adding a small amount of silicon nitride and zirconium boride can improve the strength of zirconia ceramics in high temperature environments. Carbon nanotubes are a hollow tubular structure carbon material formed by curling graphene, with fullerene hemisphere caps at both ends. Adding a small amount of graphene can improve the conductivity of the prepared composite ceramic powder. At three node temperatures of room temperature, 1170°C, and 2370°C, zirconium oxide will undergo a martensitic phase transformation and undergo a phase structure transformation of monoclinic, tetragonal, and cubic phases. During the transformation process, the volume of zirconia ceramics changes by about 5%, which may make it difficult to densify calcium oxide ceramics and cause cracking; carbon nanotubes can be used as a toughening material to connect the two surfaces of the crack to generate closing stress, hindering the continued expansion of the crack, thereby effectively enhancing its fracture toughness. The present invention adopts wet ball milling to prepare composite ceramic powder. All components of the composite ceramic powder used are hard raw materials, and the amount of water needs to be reduced; appropriately increasing the ball-to-material ratio can greatly improve the powder fineness; designing the corresponding ratio of balls, materials and water, and undergoing a specific grinding process, a composite ceramic powder with small particle size and uniform particles can be obtained.

[0021] 2. Add a small amount of binder mixture to the composite ceramic powder to prepare a feed. The binder mixture is composed of low-melting-point polyethylene wax and acrylic acid oligoester. The binder mixture is well wrapped with the composite ceramic powder. In the process of composite ceramic powder molding, it not only gives the powder good fluidity, but also plays a role in maintaining the shape of the green body after molding and during degreasing, so that it has a certain strength. In addition, due to the low melting point of the binder mixture, the degreasing temperature and degreasing time can be reduced. During the degreasing of the green body, organic solvent degreasing will leave a part of the connecting channels, causing a certain degree of microscopic and macroscopic defects. Later, metal ion elements are injected into the ceramic surface. The depth of metal ions injected into the ceramic body is different, so that it can penetrate into the ceramic body, thereby increasing the density of the ceramic body. The injection of multiple metal ions into the ceramic surface will produce fierce atomic collisions and temperature rise effects of the target, and can form multiple compounds with zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes in the ceramic body to obtain multiple alloy phases and different organizational structures, thereby improving the strength of the prepared zirconium oxide composite ceramic. Finally, a film is coated on the surface of the ceramic body injected with metal ions to improve the flatness of the ceramic surface and further enhance its own strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The present invention is a process flow chart for preparing a high-strength zirconium oxide composite ceramic product. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 This embodiment provides a preparation process of a high-strength zirconium oxide composite ceramic product, comprising the following steps: S1, preparing a composite ceramic powder: According to weight parts, 70 parts of zirconium oxide, 5 parts of silicon nitride, 1 part of zirconium boride and 1 part of carbon nanotubes are added to an intermittent ball mill for wet ball milling. The inner diameter of the intermittent ball mill is 1.5 meters, the ball milling speed is 25r / min, the ball milling time is 10h, the ball milling medium is water, and the ratio of balls, materials and water is 4:1:0.5 to obtain a composite ceramic powder.

[0026] S2. Prepare feed: According to parts by weight, 5 parts of polyethylene wax, 3 parts of methyl acrylate and 3 parts of ethyl acrylate were mixed evenly to obtain a binder mixture. The binder mixture was heated and melted on a double-roll rubber mixer, and the roller temperature was set to 105° C. until the binder mixture was completely melted between the double rollers. Then 80 parts of the composite ceramic powder was added to the double-roll rubber mixer for mixing at a mixing temperature of 120° C. and a mixing time of 25 minutes to obtain a feed.

[0027] S3, preparing ceramic body: The feed material was transferred to a mold of 20×40×20 mm, and a hydraulic press was used to pressurize one side to 130 MPa to obtain a molded green body.

[0028] The degreased green body was added into the SPS furnace and sintered in a nitrogen atmosphere; wherein, the axial pressure during sintering was 50 MPa, the sintering temperature was 1200°C, and the sintering time was 5 min, and a ceramic green body was prepared.

[0029] S4, preparing a ceramic body injected with metal ions: A metal ion implanter with a metal vapor vacuum arc source was selected, and the ceramic body was placed in the vacuum target chamber of the metal ion implanter, which was filled with argon gas. First, He ions were implanted into the ceramic body, with an implantation energy of 500 keV and an implantation dose of 1×10 17 / cm -2The He ion implantation depth is 1.25 μm. Then, B ions are implanted into the ceramic body with an implantation energy of 500 keV and an implantation dose of 1×10 16 / cm -2 The implantation depth of B ions is 0.7 μm, and a ceramic body after metal ion implantation is obtained.

[0030] S5. Preparation of a high-strength zirconium oxide composite ceramic product: The ceramic body injected with metal ions is placed in the coating chamber of a multi-arc ion coating machine equipped with a columnar arc source. The coating is carried out for 30 minutes at 400°C and 1Pa, and then the coating is stopped to obtain a TiAlN film with a film thickness of 25 mm. When the temperature of the coating chamber is cooled to room temperature, the ceramic body is taken out to obtain a high-strength zirconia composite ceramic product.

[0031] Example 2 This embodiment provides a preparation process of a high-strength zirconium oxide composite ceramic product, comprising the following steps: S1. Preparation of composite ceramic powder: According to weight parts, 75 parts of zirconium oxide, 6 parts of silicon nitride, 3 parts of zirconium boride and 3 parts of carbon nanotubes are added to an intermittent ball mill for wet ball milling. The inner diameter of the intermittent ball mill is 1.5 meters, the ball milling speed is 26r / min, the ball milling time is 11h, the ball milling medium is water, and the ratio of balls, materials and water is 6:1:0.8 to obtain a composite ceramic powder.

[0032] S2. Prepare feed: According to parts by weight, 8 parts of polyethylene wax, 4 parts of methyl acrylate and 4 parts of ethyl acrylate were mixed evenly to obtain a binder mixture. The binder mixture was heated and melted on a double-roll rubber mixer, and the roller temperature was set to 109° C. until the binder mixture was completely melted between the double rollers. Then, 90 parts of the composite ceramic powder was added to the double-roll rubber mixer for mixing at a mixing temperature of 125° C. and a mixing time of 26 minutes to obtain a feed.

[0033] S3, preparing ceramic body: The feed material was transferred to a mold of 20×40×20 mm, and a hydraulic press was used to pressurize one side to 140 MPa to obtain a molded green body.

[0034] The formed green body is transferred to a muffle furnace for segmented degreasing to obtain a degreased green body. In the first stage of degreasing, the muffle furnace is heated from room temperature to 100°C, kept at this temperature for 80 minutes, and the heating rate is 6°C / min; in the second stage of degreasing, the muffle furnace is heated from 100°C to 300°C, kept at this temperature for 40 minutes, and a degreased green body is obtained.

[0035] The degreased green body is put into an SPS furnace and sintered in a nitrogen atmosphere; wherein, the axial pressure during sintering is 50 MPa, the sintering temperature is 1250°C, and the sintering time is 8 min, to prepare a ceramic green body.

[0036] S4, preparing a ceramic body injected with metal ions: A metal ion implanter with a metal vapor vacuum arc source was selected, and the ceramic body was placed in the vacuum target chamber of the metal ion implanter, which was filled with argon gas. First, He ions were implanted into the ceramic body, with an implantation energy of 500 keV and an implantation dose of 5×10 17 / cm -2 The He ion implantation depth is 1.29 μm. Then, B ions are implanted into the ceramic body with an implantation energy of 500 keV and an implantation dose of 5×10 16 / cm -2 The implantation depth of B ions is 0.8 μm, and a ceramic body implanted with metal ions is obtained.

[0037] S5. Preparation of a high-strength zirconium oxide composite ceramic product: The ceramic body injected with metal ions is placed in the coating chamber of a multi-arc ion coating machine equipped with a columnar arc source. The coating is carried out for 40 minutes at 400°C and 5Pa, and then the coating is stopped to obtain a TiAlN film with a film thickness of 28 mm. When the temperature of the coating chamber is cooled to room temperature, the ceramic body is taken out to obtain a high-strength zirconia composite ceramic product.

[0038] Example 3 This embodiment provides a preparation process of a high-strength zirconium oxide composite ceramic product, comprising the following steps: S1. Preparation of composite ceramic powder: According to weight parts, 80 parts of zirconium oxide, 10 parts of silicon nitride, 5 parts of zirconium boride and 5 parts of carbon nanotubes are added to an intermittent ball mill for wet ball milling. The inner diameter of the intermittent ball mill is 1.5 meters, the ball milling speed is 30r / min, the ball milling time is 12h, the ball milling medium is water, and the ratio of balls, materials and water is 8:1:1 to obtain a composite ceramic powder.

[0039] S2. Prepare feed: According to parts by weight, 10 parts of polyethylene wax, 5 parts of methyl acrylate and 5 parts of ethyl acrylate are mixed evenly to obtain a binder mixture. The binder mixture is placed on a double-roll rubber mixer for heating and melting, and the roller temperature is set to 110° C. Until the above binder mixture is completely melted between the double rollers, 100 parts of the composite ceramic powder is added to the double-roll rubber mixer for mixing, the mixing temperature is 130° C., and the mixing time is 30 minutes to obtain a feed.

[0040] S3, preparing ceramic body: The feed material was transferred to a mold of 20×40×20 mm, and a hydraulic press was used to pressurize one side to 150 MPa to obtain a molded green body.

[0041] The formed green body is transferred to a muffle furnace for segmented degreasing to obtain a degreased green body. In the first stage of degreasing, the muffle furnace is heated from room temperature to 100°C, kept for 100 minutes, and the heating rate is 10°C / min; in the second stage of degreasing, the muffle furnace is heated from 100°C to 300°C, kept for 50 minutes, and the heating rate is 10°C / min to obtain a degreased green body.

[0042] The degreased green body is put into an SPS furnace and sintered in a nitrogen atmosphere; the axial pressure during sintering is 50 MPa, the sintering temperature is 1300°C, and the insulation time is 10 min, thereby obtaining a ceramic green body.

[0043] S4, preparing a ceramic body injected with metal ions: A metal ion implanter with a metal vapor vacuum arc source was selected, and the ceramic body was placed in the vacuum target chamber of the metal ion implanter, which was filled with argon gas. First, He ions were implanted into the ceramic body, with an implantation energy of 500 keV and an implantation dose of 5×10 17 / cm -2 The He ion implantation depth is 1.29 μm. Then, B ions are implanted into the ceramic body with an implantation energy of 500 keV and an implantation dose of 5×10 16 / cm -2 The implantation depth of B ions is 0.8 μm, and a ceramic body implanted with metal ions is obtained.

[0044] S5. Preparation of a high-strength zirconium oxide composite ceramic product: The ceramic body injected with metal ions is placed in the coating chamber of a multi-arc ion coating machine equipped with a columnar arc source. The coating is carried out for 50 minutes at 400°C and 10Pa, and then the coating is stopped to obtain a TiAlN film with a film thickness of 30 mm. When the temperature of the coating chamber is cooled to room temperature, the ceramic body is taken out to obtain a high-strength zirconia composite ceramic product.

[0045] Comparative Example 1 The difference between this comparative example and Example 3 is that in step S2, the binder mixture is replaced by a styrene adhesive of the same mass to prepare a feed; in the degreasing stage, the third degreasing stage is added: heating from 300°C to 500°C, keeping warm for 500 minutes, and the heating rate is 5°C / min to obtain a degreased green body.

[0046] Comparative Example 2 The difference between this comparative example and Example 3 is that in step S1, zirconium oxide and silicon nitride are used as raw materials to prepare composite ceramic powder.

[0047] Comparative Example 3 The difference between this comparative example and Example 3 is that in step S4, the implantation energy of He ions is adjusted to make the implantation depth 0.7-0.8 μm, thereby obtaining a ceramic body implanted with metal ions.

[0048] Performance Test: The high-strength zirconia composite ceramic products prepared in Examples 1-3 and Comparative Examples 1-3 were cut into sample sizes of 5×5×20 mm, and the samples were marked as Examples 1-3 and Comparative Examples 1-3, respectively.

[0049] According to GB / T6569-2006 "Test Method for Bending Strength of Fine Ceramics", the bending strength of samples of Examples 1-3 and Comparative Examples 1-3 was tested; the corners of the samples were slightly chamfered. According to GB / T16534-1996 "Test Method for Vickers Hardness of Engineering Ceramics", the Vickers hardness of samples of Examples 1-3 and Comparative Examples 1-3 was tested; the surface of the samples needed to be polished to a mirror finish. According to GB / T8489-2006 "Test Method for Compression Strength of Fine Ceramics", the compressive strength of samples of Examples 1-3 and Comparative Examples 1-3 was tested; the pressure-bearing surface of the samples needed to be flat. Specific test results are shown in Table 1 below. Table 1 - Performance test data table of samples

[0050] Data Analysis: Comparative analysis of the data in Table 1 above shows that the zirconia composite ceramics prepared in Examples 1-3 of the present invention have excellent flexural strength, Vickers hardness and compressive strength. In Comparative Example 1, the binder mixture prepared by replacing the styrene adhesive with high viscosity and high melting point not only requires a longer degreasing time and a higher degreasing temperature, but also, the molecular weight of the styrene adhesive is larger, and the pores in the ceramic body after degreasing are larger, resulting in a decrease in the flexural strength, Vickers strength and compressive strength of the prepared composite ceramic.

[0051] In Comparative Example 2, zirconium oxide and silicon nitride are used as raw materials to prepare ceramic powders, which reduces the types of raw materials for preparing ceramic powders and also reduces the mechanical properties of the prepared zirconium oxide composite ceramics, which is manifested in the reduction of the values ​​of the flexural strength, Vickers strength and compressive strength of the zirconia composite ceramics. In Comparative Example 3, the injection depth of He ions is the same as the injection depth of B ions, which is not conducive to the distribution of the two types of metal ions at different diameters of the ceramic body, thereby reducing the values ​​of the flexural strength, Vickers strength and compressive strength of the prepared ceramic body.

[0052] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0053] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0054] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing a high-strength zirconium oxide composite ceramic product, characterized in that: The following steps are involved: S1, mixing zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes, and wet-milling them to obtain a composite ceramic powder; S2, the binder mixture is placed on a roller rubber mixer and heated to melt until the binder mixture is completely melted, and the roller temperature is set to 100-105°C; then the composite ceramic powder is added and mixed at a mixing temperature of 120-130°C to obtain feed; the feed is pressurized, degreased, and sintered in a nitrogen atmosphere to obtain a ceramic body; S3, the ceramic body is transferred to a metal ion implanter, and He ions and B ions are implanted in sequence, the implantation depth of He ions is 1.25-1.29 μm, and the implantation depth of B ions is 0.7-0.8 μm, to obtain a ceramic body after metal ion implantation; The ceramic body injected with metal ions is placed on a multi-arc ion coating machine for coating, and the coating layer is a 25-30 mm thick TiAlN film, thereby obtaining a high-strength zirconium oxide composite ceramic product.

2. The preparation process of a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S1, the ratio of zirconium oxide, silicon nitride, zirconium boride and carbon nanotubes is 70-80:5-10:1-5:1-5 by weight; the ball milling speed is 25-30 r / min, the ball milling time is 10-12 h, the ball milling medium is water, and the ratio of balls, materials and water is 4-8:1:0.5-1.

3. The preparation process of a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S2, the method for preparing the binder mixture comprises the following steps: in parts by weight, 5-10 parts of polyethylene wax, 3-5 parts of methyl acrylate and 3-5 parts of ethyl acrylate are uniformly mixed to obtain a binder mixture.

4. The preparation process of a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S2, the ratio of the binder mixture to the composite ceramic powder is 11-20:80-100 in parts by weight, and the mixing time is 25-30 minutes.

5. The preparation process of a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S2, the pressure of the pressurized molding is 130-150MPa; the degreasing is staged degreasing: the first stage is heated from room temperature to 100°C and kept warm for 50-100min, and the second stage is heated from 100°C to 300°C and kept warm for 30-50min, and the heating rate is 5-10°C / min.

6. The preparation process of a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S2, the sintering temperature is 1200-1300°C, the axial pressure during sintering is 50 MPa, and the sintering time is 5-10 min.

7. The process for preparing a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S3, the He ion implantation energy is 500 keV and the implantation dose is 1×10 17 -5×10 17 / cm -2 The implantation energy of B ions is 500 keV and the implantation dose is 1×10 16 / cm -2 -5×10 16 / cm -2 .

8. The process for preparing a high-strength zirconia composite ceramic product according to claim 1, characterized in that: In step S3, the coating temperature is 400-450°C, the coating pressure is 1-10Pa, and the coating time is 30-50min.

9. A high-strength zirconia composite ceramic product, characterized in that: The high-strength zirconia composite ceramic product is prepared by using a preparation process for a high-strength zirconia composite ceramic product as described in any one of claims 1-8.

Citation Information

Patent Citations

  • Mullite-zirconia composite ceramic and production method thereof

    CN108358628A

  • Nano zirconium oxide composite material for injection molding, and preparation method and application thereof

    CN113735601A

  • Method for coating TiAlN on surfaces of titanium and titanium alloy surgical instruments

    CN102392221A

  • Wear-resisting ball with TiAlN coating

    CN104275232A

  • Preparation method of titanium-aluminum nitride coating for hot extrusion die

    CN117646167A

Cited By

  • Zirconium oxide ceramic modified by graphene / zirconium oxide calcined composite microspheres

    CN121717622A